Evaluation of the sampling methods applied to phycoperiphyton studies in the Ratones River estuary, Brazil - Vettorato,Bianca (2010)
AIM: The present study aimed on testing the efficiency of four sampling methods for identification and quantification applied in studies on the biodiversity and spatial-temporal distribution of the phycoperiphyton in the Ratones River estuary; METHODS: The sampling were carried out in three sampling stations along the Ratones River in March and August 2008. The methodologies used for the separation of the periphyton from the sediment were made with the use of sieves and trapping tissue. A removing method through manual agitation and "in situ" analysis was used for epiphytes. To evaluate the efficiency of the methodology for periphyton, data on phytoplankton was included for comparative reasons; RESULTS: The trapping method option was the most appropriate for removing the live specimens from the sediment, and to try to minimize the problems found with the other two methodologies tested. In the case of the epiphytic microalgae the best counting technique resulted from the "in situ" method; CONCLUSIONS: In summary, the results presented here support the difficulties faced in studying phycoperiphytic samples in estuaries, which are shallow and dynamic environments, and for that reason the communities occurring in these areas are constantly influenced by the sediment.